Helicobacter, Hygiene, Atopy, and Asthma - Miftahussurur, Muhammad; Nusi, Iswan A.; Graham, David Y.; Yamaoka, Yoshio (Frontiers in Microbiology, 2017)
The hygiene hypothesis links environmental and microbial exposures in early life to the prevalence of atopy, allergy, and asthma. Helicobacter pylori infection is typically acquired in childhood and acquisition of the infection is associated with poor household hygiene. Some population surveys have shown an inverse association between H. pylori infection and atopy, allergy, and asthma leading to the suggestion that H. pylori infection may be protective against disease; others consider it simply a biomarker for poor household hygiene. We review the relevant surveys, cohort studies, meta-analyses and studies testing the protective hypothesis. Overall, the results of surveys and cohort studies are inconsistent, whereas meta-analyses show a significant but weak inverse correlation. In contrast, studies directly testing the protection hypothesis in relation to asthma in populations with poor hygiene and low H. pylori prevalence failed to confirm a protective effect. H. pylori is a major cause of human disease including chronic gastritis, peptic ulcer, and gastric malignancies. H. pylori infections most likely serve as a biomarker for poor hygienic conditions in childhood. We conclude that while synergistic interactions between environmental factors in childhood are important determinants of the pathogenesis of atopy, allergy, and asthma; H. pylori is inversely related to good hygiene and thus it’s presence serves as a biomarker rather than for a specific prevention role for H. pylori or H. pylori antigens.